1/3 SIMPSON’S RULE FOR ANALYSIS OF STRUCTURE DYNAMIC RESPONSE DUE TO EARTHQUAKE LOAD - Imani, Rafki; Nasmirayanti, Rita; Sahputra, Deded Eka (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
In structural analysis, many calculations are encountered which are very complex, making it difficult to do with exact mathematical calculations. For easier analysis, numerical methods are needed to simplify the calculations. Complex building structures such as towers, multi-storey structures and other buildings, are idealized for simplification into a single degree of freedom system (SDOF), assuming that the dynamic response of structures due to earthquake loads is horizontal. The analysis of this model is correlated with numerical analysis, so it can be completed quickly. The numerical method used in this study is the 1/3 Simpson Integral Method, because this method is suitable for calculating dynamic structural responses such as structural displacement responses. The analysis procedure begins by entering the external forces on the structural system and calculating the resulting response value. The analysis can be repeated for a variety of different parameters, such as the mass of the structure, the dumping ratio and the stiffness of the structure. Structural response is calculated by sinusoidal dynamic load type for damped and undamped systems. The results of this study conclude that the relationship between the mass of the structure, the damping of the structure and the stiffness of the structure with the displacement of the structure has an inverse relationship, where with high mass, high damping and high stiffness, it can reduce the structure displacement.